Criteria for Knowledge of Fissure Sealant Material Before and After Using Online Leaflets - Ngatemi; Pudentiana Rr R. E.; Indrayati Fadjeri; Miftahul (International Journal of Science and Society, 2023)
Health problems, especially dental health, are a problem that is quite serious in Indonesia. In overcoming this dental health problem, material regarding fissure sealants can have quite an important role. This is because the presence of fissure sealant can protect teeth from caries. This research was carried out to see the level of knowledge of parents about fissure sealants through the use of online leaflets. This research will be carried out using a quantitative approach. The data used in this research was obtained through filling out a questionnaire. The results of this research then found that parents' knowledge regarding fissure sealants is still relatively low. To be able to overcome this problem, education can be carried out for parents of students. Through the results of the outreach that has been carried out, it was found that there was a significant increase in understanding regarding fissure sealant materials among parents.